El juego y su incidencia en el desarrollo psicomotor de los niños y niñas del centro de desarrollo infantil Manuel Jiménez, del barrio Santa Ana, parroquia El Lucero, cantón Calvas, provincia de Loja. Período 2011-2012 - Cuenca Yaguana, Marco Vinicio (2015)
For the present investigation was raised as general objective: determine if children's games that teachers, use affect the motor development of children's early education. It was a type of descriptive research, used methods: scientific, inductive, deductive, analytical and synthetic. Within the methodological process, the survey was applied to 2 teachers of initial education, 15 parents and an observation guide 16 children to evaluate their development psychomotor, here established problems. After processing the information of the data collected, it was determined that surveyed teachers all show that the majority of children participating in the games that they pose, there is and show a participatory part of the students behavior; cheerful and a superb level of development psychomotor, only 37.5% of children like little games that they perform, showing aggression to them.